Recognition of a Medieval Indic-‘Modi’ Script using Empirically Determined Heuristics in Hybrid Feature Space - Maurya, RK; Maurya, SR (International Journal of Computer Sciences and Engineering, 2025)
The ‘Modi’ script originated as a cursive variant of the script during the 17th century CE and used to write the Marathi language spoken in the Indian state of Maharashtra. Modi script evolved over time and found in many styles of writing. There is no standardization for writing characters and numerals of ‘Modi’ script but largely written without lifting the pen. The cursive nature of the script and lack of standardization in writing style pose challenges in digital recognition of documents written using Modi script including historical ones. Being largely medieval era script, modern document recognition systems lack support for recognizing handwritten texts using ‘Modi’ script. In this paper, we have described the framework of digital recognition of characters of handwritten ‘Modi’ script using empirically determined heuristics for determining the contribution of features from hybrid feature space for recognition of the ‘Modi’ character. The hybrid feature space uses normalized chain code together with feature vector encompassing a number of holes, endpoints, and zones associated with the character. The proposed framework for digital recognition of ‘Modi’ character using empirically determined heuristics provides a naïve model for recognizing a class of Indic scripts especially based on the cursive style of writing. The average and best recognition performance for the proposed method was measured to be 91.20% and 99.10% respectively.